Pendampingan Pembuatan Sistem Informasi Pembayaran Tagihan Air Berbasis Website Pada BUMDes ‘Saling Sedok’ Desa Peresak Kecamatan Sakra Kabupaten Lombok Timur - Lalu Kerta Wijaya; Indra Gunawan; Harianto; Ahmad Arbiansyah; Susanti; Yusril Hadi; Angghita Muthiara Yusfadhila; Muh. Kamarur Rijali Hilali; Zulkarnaen (Universitas Hamzanwadi, 2025)
The website-based water bill payment information system at BUMDes Saling Sedok is a system used to carry out tariff management, more efficient customer data management, daily and monthly reports and outstanding bills along with water meter recording. It is hoped that this water bill payment information system will make it easier for officers or managers to carry out management by storing and processing payment transaction data from existing customers. The research method used is the waterfall method in planning and development, while the power collection method uses observation and interview methods starting from analysis, planning, designing and creating a website-based water bill payment information system with the achievements of the stages that occur in managing water bill payment power. it becomes easier, more effective and efficient. The software used for program design and implementation uses xampp as the web server, phpMySQL as the database and visual studio code as the text editor for writing php and html scripts. The results of this community service research include a project to design a website-based water bill payment information system to make it easier for officers to record water bill reports such as customer data, tariff data, bill data and water meter usage data. Using information system testing with the black box testing method and the final stage is implementing the information system which includes the implementation of software, hardware, databases and interfaces of the resulting information system